2011
DOI: 10.1111/j.1365-2427.2010.02566.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of genetic diversity in the North American mayfly Ephemerella invaria associated with deforestation of headwater streams

Abstract: Summary 1. Terrestrial dispersal by aquatic insects increases population connectivity in some stream species by allowing individuals to move outside the structure of the stream network. In addition, individual survival and reproductive success (as well as dispersal) are tightly linked to the quality of the terrestrial habitat. 2. In historically forested catchments, deforestation and altered land use have the potential to interfere with mayfly dispersal or mating behaviours by degrading the quality of the terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…AV2 would be sensitive to the potentially isolating effects of forest harvesting in headwater streams based on its adult flight stage and preference for good water quality (signal score of 8: Chessman 2003). Their results suggested there was no observable impact on diversity until the level of catchment clearing reached at least 40-50%, after which diversity was found to decrease with increasing percentage area of catchment clearing (Alexander et al 2011). However, we found no significant difference between selectively harvested and non-harvested sub-catchments for any of the diversity indices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AV2 would be sensitive to the potentially isolating effects of forest harvesting in headwater streams based on its adult flight stage and preference for good water quality (signal score of 8: Chessman 2003). Their results suggested there was no observable impact on diversity until the level of catchment clearing reached at least 40-50%, after which diversity was found to decrease with increasing percentage area of catchment clearing (Alexander et al 2011). However, we found no significant difference between selectively harvested and non-harvested sub-catchments for any of the diversity indices.…”
Section: Discussionmentioning
confidence: 99%
“…A study in northern Australia on the chironomid Echinocladius martini found natural habitat fragmentation as a result of extensive historical climatic fluctuations might have isolated historical populations, driving genetic divergence in allopatry (Krosch et al 2009). One other study showed that deforestation reduced genetic diversity in a mayfly population in eastern USA as a result of habitat loss, both instream and terrestrial, and through reduced dispersal of adults (Alexander et al 2011). One other study showed that deforestation reduced genetic diversity in a mayfly population in eastern USA as a result of habitat loss, both instream and terrestrial, and through reduced dispersal of adults (Alexander et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other disturbances, such as fire (Brown et al 2001) and deforestation (Alexander et al 2011), occur over areas of the landscape that are not constrained by the dendritic river network. Because the movements of obligate aquatic organisms are constrained to the river channel, these terrestrially based disturbances can lead to a mismatch 350 between the geometry of dispersal pathways and the geometry of landscape disturbances (Fagan 2002).…”
Section: Habitat Alteration and Lossmentioning
confidence: 99%